Rapid Prototyping of Microfluidics Devices using Xurograhy Method - Fiona Ling, Wang Ming; Wafaa, Kamil Mahmood; Abdulbari, Hayder A. (EDP Sciences, 2017)
Rapid prototyping of microchannel gain lots of attention from researchers along with the rapid development of microfluidic technology. The conventional methods carried few disadvantages such as high cost, time consuming, required high operating pressure and temperature and involve expertise in operating the equipment. In this work, new method adapting xurography method is introduced to replace the conventional method of fabrication of microchannels. The novelty in this study is replacing the adhesion film with clear plastic film which was used to cut the design of the microchannel as the material is more suitable for fabricating more complex microchannel design. The microchannel was then mold using polymethyldisiloxane (PDMS) and bonded with a clean glass to produce a close microchannel. The microchannel produced had a clean edge indicating good master mold was produced using the cutting plotter and the bonding between the PDMS and glass was good where no leakage was observed. The materials used in this method is cheap and the total time consumed is less than 5 hours where this method is suitable for rapid prototyping of microchannel.